Analisis Strategi Pembelajaran Bahasa Jepang Dasar di LPK Fuji Academy Bali Cabang Denpasar - ida adnyani; Ni Nengah Suartini; Yeni Yeni (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
This study aims to describe the effective strategies used in basic level Japanese learning at LPK Fuji Academy Bali Denpasar Branch, and the factors underlying the use of these learning strategies. This is a descriptive qualitative research.The subject in this research is one of the teachers and Karasu class. Data collection methods used by observation, interviews, and documentation. The data analysis technique in this research is qualitative descriptive analysis. The results showed that effective strategies used in basic Japanese learning activities are innovative learning strategies of TPS (Think-Pair-Share) type, role play, gossiping groups activity, DRTA (Direct-Reading-Thinking-Activity), mind maps, key words pictorial, guessing from context, EEE (Exploration-Explanation-Expressing), Karuta game, and tongue twister. The textbooks used in basic Japanese learning activities are Minna no Nihongo 1 and 2, and Irodori shokyuu 1 and 2. The various factors underlying the use of these strategies are internal and external factors, the use of stimulus to avoid learning boredom, reinforcement of learning to maximize language skills, and efforts to improve student learning outcomes. Keywords : Language Learning Targets, Basic Learning Strategies, Job Training Institute, Irodori, Minna no Nihongo.